Dynamic response of submerged floating tunnels with dual sections under irregular waves. (1st December 2021) - Won, Deokhee; Seo, Jihye; Kim, Seungjun
Abstract: A type of submerged floating tunnel (SFT) with a dual section was proposed in this study, and its hydrodynamic behavior was investigated using an analytical method. Unlike existing SFTs with a single section, a dual-SFT with two tunnel bodies requires the analysis of various aspects. To this end, the use of a finite element analysis technique was verified by comparison with previously reported hydraulic test results. Based on this, a free vibration analysis and parameter study were conducted for the dual-SFT under irregular waves. The behavior characteristics of the SFT were analyzed by selecting representative variables, such as the buoyancy-weight ratio (BWR), current speed, spacing of the tunnel body, and wave steepness. The results confirmed that the BWR, wave steepness, tunnel spacing, and current flow values for which slack occurred changed according to the tether-mooring method. In addition, the resistance characteristics under waves and currents were very dissimilar according to the two proposed mooring methods. Highlight: This study presented the hydrodynamic behavior of the dual submerged floaiting tunnel(SFT) by a finite element analysis. Compared to a general single tunnel, the dual-SFT exhibited more sensitive behavior according to the spacing of the tunnel body, tether mooring method, BWR, wave steepness, etc.